Pemberdayaan Ibu Rumah Tangga Memamfaatkan Barang Bekas Untuk Meningkatkan Pendapatan Keluarga Pada Kelompok Binaan Koperasi Anisa Di Dususn Monjok Kebon, Kota Mataram - Sulaimiah; Sulhaini; Harmi Widiana; Bq.Ismiwati (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Community service carried out by the Anisa cooperative in the village of Monjok Kebon, Mataram City, has improved the community's ability to manage the potential of their village, particularly by turning used items into attractive household items. These items are not only targeted at the lower economic class but also at the upper economic class as attractive household items that are smooth, and highly functional for household needs, such as hoes, shovels, crowbars, stoves, plates, mirror frames, photo frames, wall decorations, and so on. The sales target is not limited to the surrounding community but extends further through online sales. Starting from production by sourcing high-quality raw materials, followed by the production process handled by skilled employees, and attractive packaging. The village has great potential and requires proper guidance to produce products of superior quality compared to competitors. In this community service initiative, training is provided on production and workforce development to ensure employees possess the skills required by the cooperative's supported groups. It is essential for employees to have a strong entrepreneurial spirit, be diligent in their work, and prioritize the quality of the products produced. A better understanding of marketing, creating attractive packaging, and maintaining detailed record-keeping are also emphasized. Training is needed to make employees more skilled and detail-oriented in production, understand good human resource management, competent marketing, adequate financial management, and conduct online sales to expand the sales reach. In this training, guidance from the community service team is required, as well as providing guidance in participating in product exhibitions conducted in collaboration with relevant agencies